La documentación del gabinete de antigüedades de la Real Academia de la Historia y su contribución a la Numismática Hispánica: El ejemplo de los «tesorillos» de Azuara - Rodríguez Casanova, Isabel (Revista General de Información y Documentación, 2007)
Some finds of Celtiberian coin-hoards from Azuara (Zaragoza) were published in the second half of the 19th century and in the 20th century. In this article, based on some documents conserved in the Real Academia de la Historia of Madrid, the authoress tries to clarify some confuse news about the finds which have been repeated in subsequent numismatic literature.